Reconstruction of Arrangements on the Role of the Financial Services Authority in Bank Health Supervision Post-Law on Development and Strengthening of the Financial Sector (International Journal of Religion, 2024)
The banking industry plays a significant role in supporting the stability and growth of the national economy. To ensure the sound and secure operation of banking activities, effective oversight from an independent institution is necessary. This study aims to analyze the reconstruction of the regulatory role of the Financial Services Authority (OJK) in supervising bank health following Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector. Using a normative approach, this research examines relevant legislation, particularly Law Number 4 of 2023, and analyzes related legal cases. Through literature review and secondary data analysis, this study seeks to uncover the reconstructed regulatory role of the OJK in maintaining the health of banking institutions after the enactment of this law. The research findings indicate that Law Number 4 of 2023 strengthens the independence and authority of the OJK in overseeing bank health. This law reaffirms the OJK's authority to issue licenses, regulate financial aspects, conduct both direct and indirect supervision, impose sanctions, and protect banking consumers. Additionally, there are new powers, such as the institutional strengthening of the OJK, improving governance and public trust, and enhancing financial literacy and inclusion. An analysis of related legal cases shows that this regulatory reconstruction is necessary to enhance supervisory effectiveness and ensure that banking institutions comply with prudential principles. However, there are still considerable public complaints regarding banking services, indicating a need for improvements in the OJK's supervisory implementation. Therefore, further studies are required to comprehensively reconstruct the regulations so that the OJK's role can be maximized in maintaining financial sector stability and protecting public interests.